PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI, DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Ernie Riswandari; Jefri Tamara (Universitas Bunda Mulia, 2017)
This study aims to determine the effect of recognition of revenue, operating cash flow and profitability on net income returned to shares in companies registered in Indonesia stock exchange in 2005-2008, either partially or in parallel. The research method used is multiple linear regression analysis (multiple regression), followed by statistical testing of research variables. Prior to conducting the regression analysis test lienar normality, multicollinearity, heteroscedasticity test, and autocorrelation test with the test results are not biased and inefficient. Results showed that overall from 2005 until 2008, no significant profits partially to the stock return. operating cash flow was also no significant effect on stock returns in part, Net Profit Margin portion having a significant impact on the income shares of manufacturing firms over the period 2005-2008. Simultaneously, the accounting profit, operating cash flows, and net profit margin has a significant impact on revenue share.Key Word : Laba Akuntansi, Arus Kas Operasi, Net Profit Margin, Return Saham, Perusahaan Manufaktur